1999
DOI: 10.1002/(sici)1097-4547(19990915)57:6<801::aid-jnr5>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity and transcription of proinflammatory cytokines, IκBα, and iNOS in the mouse brain during acute endotoxemia and chronic infection with Trypanosoma brucei brucei

Abstract: Trypanosoma brucei brucei (Tbb) infection is a model of chronic immune response associated with severe neurological disorders believed to lead to coma and death. We hypothesized that exaggerated production of proinflammatory molecules within the cental nervous system (CNS) may be involved in the etiology of the disease, i.e., African Tripanosomiasis. The purpose of the present study was therefore to verify the effects of the parasite Tbb on the genetic expression of the immediate-early gene c-fos (index of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…In contrast, IL-6 gene expression was found in the CNS of only a few mice and it was not considered significant (Table I). It should be noted that we previously demonstrated that this IL-6 probe hybridizes IL-6 in the brain of LPS-treated mice (43). For TNF-␣, a weak (ϩ) mRNA expression appeared at 24 h p.i.…”
Section: Expression Of Proinflammatory Cytokines and Chemokines In Thmentioning
confidence: 72%
“…In contrast, IL-6 gene expression was found in the CNS of only a few mice and it was not considered significant (Table I). It should be noted that we previously demonstrated that this IL-6 probe hybridizes IL-6 in the brain of LPS-treated mice (43). For TNF-␣, a weak (ϩ) mRNA expression appeared at 24 h p.i.…”
Section: Expression Of Proinflammatory Cytokines and Chemokines In Thmentioning
confidence: 72%
“…These data suggest a pattern of LPS-induced MCP-1 expression that begins in the periphery and spreads to the brain, first in areas that are in contact with peripherally circulating inflammatory mediators and then throughout other areas of the brain. Other inflammatory mediators also follow a similar site-specific pattern of expression after peripheral LPS, including cyclooxygenase-2, TNF-α, IL-1β, inducible nitric oxide synthase and Iκ Bα, where these molecules are first upregulated in the choroid plexus, circumventricular organs, and/or near blood vessels [ 7 , 38 - 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The slices were mounted onto poly-L-lysine-coated slides and stored at -20 C until used. In situ hybridization using a TNF-a 35 S-labeled cRNA probe and immunohistochemistry using anti-MIP-2 antibody (PharMingen) were performed as described [42].…”
Section: In Situ Hybridization and Immunocytochemistrymentioning
confidence: 99%